Substance Abuse and its Implications in 21st Century - Humza, Namra (Advances in Social Sciences Research Journal, 2023)
Drug misuse poses a risk to the person as well as to society. Human resource (HR) executives and other professionals play a crucial role in adopting recommendations for policies and procedures related to drug and substance misuse in the workplace since concerns linked to alcohol and substance addiction are on the rise in the workplace. High health insurance claims, diseases, work-related injuries, reduced productivity, bad morale, and absenteeism are organizational losses. These losses do not account for the expense of managing workplace alcohol and drug addiction problems or the unquantifiable misery of the affected families and other workers. Therefore, this research focuses on how drug usage affects Pakistani youth and suggests ways to deal with this widespread problem as soon as possible.